Cata-condensed heteroannulated coronenes via selective bromination of diarenoperylenes as the key step - Yang, Xuan; Rominger, Frank; Mastalerz, Michael (Organic letters, 2018)
A facile three-step synthetic route to heteroannulated extended coronenes via a selective bromination of diarenoperylenes as the key step is presented. The heteroannulated coronenes were characterized by X-ray crystallography and by photophysical and electrochemical means.
Gesehen am 29.04.2020